Deep Image Segmentation Using Explainable Attention Mechanisms: Applications in Biomedical Imaging - M. Mushgil, Hanaa; Saad Al-Mukhtar, Farah; Qahtan Ahmed, Ehsan; Saeed Abduljabbar, Khairiyah (Al-Nahrain Journal of Science, 2025)
Correct and discernible segmentation of an image is an important part of biomedical imaging, especially when anatomical structures and pathological regions are identified. Although deep learning architectures, like U-Net and its variants, have performed well, their lack of interpretability, transparency and contextual reasoning has limited their clinical adoption. This research helps to overcome the most important issue of high-performance medical segmentation by introducing a new explainable framework that combines convolutional encoders with transformer-based decoders and dual attention mechanisms. There are three aspects of this work, based on the following objectives. (1) To boost the performance of segmentation by means of hybrid local-global feature modelling; (2) To bring about clarity through visual explanation tools; and (3) To conduct clinical viability checks through expert assessments. The architecture proposed includes CBAM for fine spatial and channel attention and combines Grad-CAM++ and SHAP for local and global explainability. Such modules make it possible for clinicians to view the decision paths of models and establish trust in automated outputs. Experiments in two datasets, which were publicly available, were performed: ISIC 2018 for skin lesion segmentation and BraTS 2021 for brain tumor segmentation. The quantitative results show that the suggested method is better than several strong baseline models, such as U-Net, Attention U-Net, and TransUNet, delivering Dice scores of 0.902 and 0.895 on ISIC and BraTS datasets, respectively. Visual comparisons and expert confirmation validate the clinical plausibility of the predicted masks and demonstrate the potential worth of the explainability in high-stakes healthcare conditions. On the whole, this work provides a prudent, precise and explainable deep learning approach toward medical image segmentation and offers ample room for scientific integration and trust-conscious implementation in diagnostics workflows.